The Impact of the COVID-19 Pandemic on the Diagnosis and Epidemiology of Type 1 Diabetes in Children - Kapelka, Klaudia; Pyrtek-Kajzer, Karolina; Sobański, Dawid; Jabłoński, Wiktor; Perek, Adam; Raszewska, Julia; Świerczek, Julia Anna Świerczek; Targosz, Weronika; Mandera, Gabriela; Wesołowska, Aleksandra (Quality in Sport, 2026)
Background: The SARS-CoV-2 pandemic strained pediatric networks, disrupting the presentation and monitoring of chronic metabolic conditions. Aim of the study: This evaluation compiles global evidence on shifts in new-onset pediatric type 1 diabetes (T1D) incidence, DKA severity, seasonal deviations, and entry parameters during the COVID-19 era. Material and methods: Data were harmonized from 14 global cohorts, capturing clinical profiles for >150,000 pediatric and adolescent subjects across the US, UK, Germany, Italy, Spain, Israel, and Canada. Results: Multi-country datasets confirmed a significant 9.5% to 35% baseline expansion in new-onset T1D, with acute DKA frequencies peaking between 39.4% and 68.2% at admission. Metabolic decompensation advanced during lockdowns, marked by a downward shift in venous pH, a high frequency of clinical shock, and a substantial rise in glycated hemoglobin (HbA1c) at 13.0 ± 1.71%. Interrupted time-series models confirmed that indirect structural disruptions—such as containment-driven care delays—operated as the primary driver of advanced decompensation, rather than direct viral pathways. Vaccination interventions subsequently lowered post-pandemic trends among adolescent groups. Conclusions: The pandemic accelerated pediatric diabetes severity due to widespread care delays. Mitigating future global shocks requires optimized screening rules, flexible intensive care insulin protocols, and remote telehealth networks.